Hubungan Pengetahuan Gizi, Sarapan, dan Uang Saku dengan Pemilihan Jajanan Siswa Overweight MIN 2 Magetan - Aziza, Amalia Yusrin; Sulandjari, Siti; Afifah, Choirul Anna Nur; Pratama, Satwika Arya (Universitas Muhammadiyah Semarang, 2024)
ABSTRACTBackground: Overweight and obesity are significant health concerns characterized by excessive fat accumulation, and they are increasingly impacting school-aged children. A major factor contributing to this issue is poor snacking behavior, as many children make snack choices that fail to meet healthy food standards. It's essential to address these habits to promote better health outcomes.Objectives: This research aims to establish the correlation between nutritional knowledge, breakfast habits, and the amount of pocket money with snack choice behavior in overweight 4-6 graders of MIN 2 Magetan.Method: The research utilized a cross-sectional design involving 57 students. Nutritional knowledge was assessed through tests, while information about breakfast habits, pocket money, and snack choices was gathered using questionnaires. The Spearman rank correlation test was utilized to analyze the dataResults: The results indicated that a majority of respondents exhibited a lack of nutritional knowledge (50.9%), maintained adequate breakfast habits (49.1%), received a moderate amount of pocket money (73.7%), and demonstrated a level of behavior focused on choosing healthy snacks (40.4%).Conclusion: The analysis indicated that there was no significant correlation between nutritional knowledge and snack selection behavior (p=0.066). Likewise, no correlation was identified between breakfast habits and snack selection behavior (p=0.932). In contrast, a significant correlation was observed between the amount of pocket money available and snack selection behavior (p=0.037).Keywords: Overweight, School-aged Children, Knowledge, Breakfast, Pocket Money, Snack Choosing Behavior